Verb between Arabic and Chinese: Contrastive study in terms of tense and aspect - Wang, Ziyu; Belajaeed, Mariam Saeed (Al-Adab Journal, 2022)
The research seeks to present a contrastive study of the three-letter simple verbs between Arabic and Chinese in order to know the tense and aspect of verbs between Arabic and Chinese, and also clarify the similarities and the differences between them in the tense and aspect of verbs destination. This research will follow the contrastive approach, and will be divided into three sections. The first topic will be concerned with the theoretical foundations which related on this topic and the differences between the types of verbs in Chinese language and Arabic language; Because Arabic is an inflectional language, the form of its words changes according to different grammar. As for Chinese, it is an isolating language, so its word form is always fixed and does not change. The second and third sections will be in a detailed interview of the verb form between Chinese and Arabic in two grammatical categories: the verb tenses (past, present and future) and the verb of the aspect (Perfective aspect, imperfective aspect and habitual aspect... etc.), as the Chinese language is not affected by the change of time, gender or number, but these meanings are embodied by arranging their words or adding some word tools, and Arabic embodies them in the conjugation of the verb.